Respiratory and muscular effects of a physiotherapy protocol carried out during hemodialysis in individuals with chronic renal failure: preliminary results. - Mayara Simões; Michele Lima Gregório; Moacir Fernandes de Godoy; Marilita Falângola Accioly (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aim: To analyze whether the proposed physiotherapy protocol during hemodialysis (HD) increases knee extensor muscle strength, palmar grip strength, respiratory muscle strength, lung function, and functional capacity of individuals with Chronic Renal Insufficiency (CRI) on HD. Methods: A preliminary results study, in which physical therapy intervention was performed in 11 subjects (49.2 ± 8.6 years) with CRI on HD treatment. Initially, Heart Rate Variability (HRV) was collected, with the individual at rest, for 15 minutes, and later, HRV linear and non-linear analyses were performed using HRV Kubios Premium Software. The protocol was performed in the first two hours of the HD session, three times a week for eight weeks, consisting of respiratory exercises, aerobic exercises, and electrical stimulation associated with progressive resistive exercises. The variables evaluated were respiratory muscle strength, knee extensor muscle strength, palmar grip strength, lung function, and functional capacity. Student's t-tests for paired samples and Wilcoxon's tests for non-parametric samples were used considering a significance level of 5%. Results: There was a significant increase in expiratory muscle strength (p = 0,012; Cohen's d = 0,59), knee extensor muscle strength (p = 0,025; Cohen's d = 0,77), palmar grip strength (P = 0,001; Cohen's d = 0,52) and functional capacity (P = 0,009; Cohen's d = 0,83). Conclusion: The proposed protocol is effective in increasing knee extensor muscle strength, palmar grip strength, expiratory muscle strength, and functional capacity of individuals with CRI on HD.